A földvásárlás és birtoklás főbb kérdései Magyarországon - Vincze-Lendvai, Edina (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In Hungary the land-purchasing is not too active business. The prices are have been growing since 2004, but they are not really high. After the EU-accession the new states got moratórium, until 2011. In the study I have analyzed the situation of the Hungárián regulation of the land-owning, the change of the land- price, the alteration of the land-market after 2004.1 have examined and compared the example of the other unión states.